The synthesis and reactivity of binuclear μ-hydrocarbyl complexes of some transition metals - Mapolie, Selwyn Frank (Department of Chemistry, 2016)
The new μ-(l,n)-alkanediyl compounds [(ƞ⁵-C₅R₄Me)Fe(CO)₂ ]₂{μ-(CH₂)n}, (R = H, n = 3 -10 and R =Me, n =3 - 6), [Mn(CO)₅]₂{μ-(CH₂)n} (M = Mn, n = 4-6 and M = Re, n= 3 and 4) have been prepared using essentially two synthetic routes. Thus the iron compounds were synthesized by the reaction of Na[(ƞ⁵-C₅R₄Me)Fe(CO)₂ ] with the appropriate dibromoalkane. The manganese and rhenium compounds on the other hand, were prepared by the decarbonylation of the corresponding diacyl compounds of the type, [M(CO)₅]₂{μ-CO(CH₂)nCO} (M = Mn or Re). These diacyl species in turn were synthesized by the reaction of Na[M(CO)s] with diacyl chlorides. All the new compounds have been fully characterized by microanalysis, infrared, ¹H and ¹³C nmr spectroscopy. The mass spectra of the compounds have been investigated and the fragmentation patterns are discussed and compared with other known polymethylene compounds. An extensive investigation into the reactivity of the new alkanediyl compounds has been carried out. Thus for example the reactivity of the compounds [CpFe(CO)₂]₂{μ-(CH₂)n} with nucleophiles such as tertiary phosphines and isocyanides, yield diacyl compounds of the type [CpFe(CO)L]₂{μ-CO(CH₂)nCO} (Cp = C₅H₄Me or C₅Me₅) and (L = tertiary phosphine or isocyanide). Similar ligand induced CO insertion reactions were observed for the manganese and rhenium alkanediyl compounds. The products from these reactions were characterized using the analytical techniques mentioned earlier. The reactions are discussed and compared with those of mononuclear alkyl compounds of manganese, rhenium and iron. The reactions of some polymethylene bridged compounds with synthesis gas have also been investigated. This reaction is of importance in view of the fact that polymethylene bridged compounds have been implicated in a number of catalytic processes e.g the Fischer- Tropsch reaction. The reaction with synthesis gas was found to yield bifunctional alcohols of the type HO(CH₂)nOH. In a separate study, the binuclear μ-phthaloyl compounds of manganese, rhenium,iron,molybdenum,cobalt and rhodium were prepared and characterized. The phthaloyl compounds of manganese, rhenium and iron were decarbonylated to form the corresponding μ-phenylene compounds. The reactions of some of these compounds with nucleophiles and electrophiles have been studied and the results compared with that of the corresponding mononuclear benzoyl and phenyl compounds.